Produção de ácido láctico a partir da casca de arroz - Montipó, Sheila (2012)
Lignocellulosic agroindustrial wastes, such as rice husks (RH), are abundant, low cost, renewable sources, available to biotransformation in value-added products. Thus, the main objective of this study was to investigate the use of RH with the purpose of its biotransformation in lactic acid (LacA) starting from hydrolysates of this residual biomass. At the same time, aiming to contribute to the mitigation of the growing environmental concern about the illegal disposal of this waste in the State of Rio Grande do Sul the biggest Brazilian rice producer. For this, a central composite rotational design (CCRD) of the hydrolysis experiments of RH in pressurized conversion system with diluted HCl and H2SO4, revealed that experiments conducted at 175 °C, for 46 min, with acid concentrations of 2.2% v v-1, generate the highest glucose contents. For hydrolysis involving HCl, 17.8 g glucose L-1, with an yield of 106.6 mg glucose g-1 RH; for hydrolysis with H2SO4, 14.1 g glucose L-1, with an yield of 84.5 mg glucose g-1 RH. Previous fermentative experiments were carried out with the aim to select resilient and efficient micro-organisms for the LacA production and, also, to evaluate the need of supplementation of the RH hydrolyzate with specific nutrients. L. rhamnosus, in this study, was the most suitable bacteria for the lactic fermentation, among all the Lactobacillus tested, being able to to produce 5.6 g LacA L-1, with a yield of 33.8 mg LacA g-1 RH (hydrolysed with HCl, without nutrient addition, 96 h fermentation). The acid hydrolysis, in this particular case, was carried out at 160 °C, for 70 min, using 4.0% HCl v v-1, generating 14.7 g glucose L-1. The lactic fermentation via CCRD was batch conducted in 4 mL vials, at 37 °C, pH 6.0, using L. casei subsp. rhamnosus ATCC 10863, specialized in catabolization of both hexoses and pentoses (except arabinose). Experiments with RH hydrolysates containing nutrients added produced up to 18.8 g LacA L-1 (maximum yield of 997,1 mg LacA g-1 sugars) in substrate hydrolyzed with HCl, after 52 h fermentation; and 14.6 g LacA L-1 (maximum yield of 999.8 mg LacA g-1 sugars) in substrate hydrolyzed with H2SO4, after 24 h fermentation. Therefore, in this study, the choices of most influence in the LacA production were fermentation with sulfuric acid and employment of L. rhamnosus.